"Internet Plus" Sports Industry of New Business Development Model. (5th August 2022) - Yang, Xiaofang
Abstract : In recent years, with the development of information technology, "internet plus" has become the main way to promote the development of sports industry, and keeping the sustainable development of sports has also become the most challenging topic in the sports field. In order to solve the sustainable development of sports industry, this paper analyzes the problems of traditional sports industry in product types, marketing models and management, and applies "internet plus" to sports industry, forming new industries such as Internet broadcasting, intelligent software and hardware, e-commerce, and e-sports, realizing humanized and intelligent products, diversified organizational forms, and innovative management models. Through the connotation and classification of "internet plus sports, " it integrates and analyzes the new format. The results show that the innovative development of new formats can be realized through product and business integration, product positioning optimization, and active industry guidance, and a "high+new" industrial structural development model can be formed. On the basis that the government and market mechanism do not conform to the economic development, through the optimization of collectivized industrial organization, a "collectivized" organizational model has been formed, and a new format of "internet plus" sports industry has been constructed. The research results have laid a solid theoretical foundation for the development of "internet plus sports."